Investigations into food web structure in the Beaufort Sea - Stasko, Ashley D. (University of Waterloo, 2017)
The effects of climate change on marine ecosystems are most pronounced in the Arctic, where ice free summers have been predicted to occur by mid-century. Climate-related changes to sea ice phenology, oceanographic habitat characteristics, and primary production regimes will likely have strong effects on ecosystem structure that could alter energy pathways, species distributions, food web dynamics, and secondary production. Knowledge of many offshore Arctic ecosystems remains poor, undermining the ability to predict the effects of a changing climate on food web structure and function. This thesis capitalizes on the first comprehensive offshore sampling program in the Canadian Beaufort Sea and Amundsen Gulf to address substantial knowledge gaps regarding fish and invertebrate food web structure in the region. Trophic structure and benthic-pelagic linkages for biological communities on the continental shelf and slope were examined using stable isotope values measured in 127 fish and invertebrate taxa, biomass distributions, and a database of biological functional traits compiled for 166 taxa. Four empirical studies were conducted to test hypotheses regarding the responses of trophic structure to environmental gradients of depth, organic matter input regimes, water mass structure, and benthic food supply. Understanding food web structure and its link to large-scale environmental gradients will be key to assessing and predicting the effects of climate change on offshore marine communities in the Canadian Beaufort Sea and Amundsen Gulf. In Chapter 2, benthic-pelagic coupling via active biological transport was identified as important for sustaining fish communities in the Beaufort Sea. Lower availability of benthic resources with increasing depth restricted biomass production for small size classes of fish in deep habitats. In those same fish communities, pelagic subsidies obtained by benthopelagic fishes were important for maintaining a relatively high biomass of large-bodied fish in deep habitats. When fish and invertebrates were considered together in Chapter 3, benthic-pelagic coupling weakened eastward alongshore, across three regions. Benthic-pelagic coupling was (1) highest west of the Mackenzie River where sinking flux of pelagic particulate organic matter (POM) is known to be relatively high, (2) intermediate on the Mackenzie Shelf where riverine inputs of terrestrial organic matter dominate the sediment, and (3) lowest in the Amundsen Gulf where strong pelagic grazing is known to limit POM sinking flux to the benthos. Within all regions considered, benthic-pelagic coupling was consistently weakest in slope habitats underlying the transition between Pacific- and Atlantic-origin waters, where much of the organic carbon is transformed or intercepted in the water column. Analyses in Chapter 4 indicated that the dominance of terrestrial POM discharged from the Mackenzie River in the Beaufort Sea dampened depth-related changes in the δ15N values of suspension/filter feeders, infaunal deposit feeders, and bulk sediment. In contrast, a faster rate of change in consumer and sediment δ15N with depth was observed in the Amundsen Gulf. Relatively high primary production in the Amundsen Gulf likely promoted intensified biological transformation of autochthonous POM in the pelagic zone and lower downward POM flux, causing greater change in POM δ15N. Surprisingly, when isotopic diversity was weighted by species biomasses in Chapter 5, most benthic communities in the Canadian Beaufort Sea and Amundsen Gulf were found to rely on similarly diverse ranges of sedimentary organic matter, regardless of the sources. Trait-based functional diversity indicated that shelf edge communities maintained a relatively high diversity of biological trophic traits, presumably to exploit pulsed food inputs associated with dynamic shelf break hydrography. Several lines of evidence supported a role for episodic food inputs in structuring shelf edge trait composition. However, pairwise relationships between trophic traits and indicators of benthic food supply were not significant at the regional scale. Functional redundancy was low across most of the region, suggesting benthic food web function will be sensitive to species loss. The research in this thesis presents the first comprehensive empirical studies of benthic food web structure for offshore fish and invertebrate communities in the Canadian Beaufort Sea and Amundsen Gulf. Each study proposes causal explanations for spatial patterns in food web structure based on data for habitat characteristics, species biomass distributions, and previously documented physical and biological properties of the regions. Three emergent properties are identified: (1) the Canadian Beaufort Sea and Amundsen Gulf should be considered separate but interconnected ecosystems, (2) organic matter pathways are key properties that define and determine trophic structure in the study systems, and (3) local habitat complexity interrupts linear associations between environmental gradients and trophic structure at the regional scale. The research represents a significant advancement in our knowledge of food webs in a rapidly changing, and understudied ecosystem. Several significant implications for ecosystem-based management are outlined in the General Conclusions section. Further study is needed to identify species-specific feeding relationships, understand how functional food web structure relates to indicators of ecosystem function, characterise winter ecology, and, ultimately, to develop an over-arching food web model that can be used to predict the impacts of a changing benthic food supply and species loss on community structure and function.
Keywords: food web; oceanography; benthic invertebrates; marine fish; stable isotopes; ecosystem structure and function; Beaufort Sea; Arctic